A Comparative Study of Segmentation Techniques used in Handwritten Documents - Bhopi, SA; Singh, MP (International Journal of Computer Sciences and Engineering, 2025)
Handwritten document image segmentation is key step for OCR (Optical Character Recognition) System. It is an important step because inaccurately segmented text lines will cause errors in the recognition stage. The selection of segmentation algorithm being used is the essential factor in deciding the accuracy of the OCR system. Devnagari is the most popular script in India. Devnagari is the script for Sanskrit, Hindi, Marathi, Kashmiri, Sindhi, Bihari, Bhili, Konkani, Bhojpuri and Nepali languages. It has vowels, consonants, vowel modifiers and compound characters, numerals. Optical Character Recognition for Devanagari is highly complex due to its rich set of conjuncts. The nature of handwriting makes the process of text line segmentation very challenging. Several techniques to segment handwriting text line have been proposed in the past. Our purpose is to provide a learning-based approach for segmentation of handwritten document images. This paper presents a quantitative comparison of three algorithms for page segmentation: Projection Profile, Run-length Smearing and Bounding Box along with some morphological operations like erosion, dilation etc. We have implemented these algorithms on our own dataset of handwritten documents. We have experimented and compare the accuracy and results of these methods.